Increasing Area Deprivation and Socioeconomic Inequalities in Heart Disease, Stroke, and Cardiovascular Disease Mortality Among Working Age Populations, United States, 1969-2011 - Gopal K. Singh, PhD; Mohammad Siahpush, PhD; Romuladus E. Azuine, DrPH, RN; Shanita D. Williams, PhD, RN, MPH (Global Health and Education Projects, Inc., 2014)
Objectives:  We examined the extent to which area- and individual-level socioeconomic inequalities in cardiovascular-disease (CVD), heart disease, and stroke mortality among United States men and women aged 25-64 years changed between 1969 and 2011. Methods:  National vital statistics data and the National Longitudinal Mortality Study were used to estimate area- and individual-level socioeconomic gradients in mortality over time. Rate ratios and log-linear and Cox regression were used to model mortality trends and differentials. Results:  Area socioeconomic gradients in mortality from CVD, heart disease, and stroke increased substantially during the study period. Compared to those in the most affluent group, individuals in the most deprived area group had, respectively 35%, 29%, and 73% higher CVD, heart disease, and stroke mortality in 1969, but 120-121% higher mortality in 2007-2011. Gradients were steeper for women than for men. Education, income, and occupation were inversely associated with CVD, heart disease, and stroke mortality, with individual-level socioeconomic gradients being steeper during 1990-2002 than in 1979-1989.  Individuals with low education and incomes had 2.7 to 3.7 times higher CVD, heart disease, and stroke mortality risks than their counterparts with high education and income levels. Conclusions and Global Health Implications:  Although mortality declined for all US groups during 1969-2011, socioeconomic disparities in mortality from CVD, heart disease and stroke remained marked and increased over time because of faster declines in mortality among higher socioeconomic groups.  Widening disparities in mortality may reflect increasing temporal areal inequalities in living conditions, behavioral risk factors such as smoking, obesity and physical inactivity, and access to and use of health services. With social inequalities and prevalence of smoking, obesity, and physical inactivity on the rise, most segments of the working-age population in low- and middle-income countries will likely experience increased cardiovascular disease burden in terms of higher morbidity and mortality rates. Key words:  CVD mortality • Heart Disease • Stroke • Deprivation • SES • Work force. Copyright © 2015 Singh et al.  This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.